(untitled) (African Journal of Law and Politics, 2023)
REDD+ – the international climate change mitigation initiative for financing the conservation of tropical forests, has generated concerns about the effect of large influxes of funds on among other things, the rights and livelihoods of forest-dependent peoples. This article sets out to demonstrate that although the international climate change legal regime has adopted the REDD+ safeguards to prevent the negative effects of REDD+ implementation on the rights and livelihoods of forest-dependent peoples, the adequacy and legal status of such leave much to be desired. A mix of empirical and doctrinal legal research methods was adopted to investigate and make a content analysis of relevant primary and secondary data on REDD+ social safeguards in order to determine the adequacy and legal status of REDD+ social safeguards and the implications for the rights and livelihoods of forest-dependent peoples. Our findings reveal that the REDD+ social safeguards are inadequate as some of the most important concerns notably, land and forest tenure rights that underpin the success of REDD+ in achieving not only its main goal of reducing forest-based carbon emissions, but also its trade-offs of protecting the rights and livelihoods of forest-dependent peoples, are not comprehensively addressed. We also found out that the REDD+ social safeguards are not legally binding on governments and REDD+ project implementer to respect the rights and livelihoods of forest-dependent peoples, putting the rights and livelihoods of forest-dependent peoples at risk. Consequently, the article recommends that countries should make the Cancun REDD+ social safeguards binding and legally enforceable by not only domesticating and integrating them into national legislation, but should also define additional safeguards and elaborate them comprehensively to guard against all possible harm or risk that REDD+ activities can cause to the rights and livelihoods of forest-dependent peoples.